Growth of GaN on sputtered GaN buffer layer via low cost and simplified sol–gel spin coating method. (September 2015) - Fong, C.Y.; Ng, S.S.; Yam, F.K.; Abu Hassan, H.; Hassan, Z.
Abstract: GaN thin film was deposited by sol–gel spin coating method with a sputtered GaN buffer layer. The structural, morphological and optical characteristics of the sputtered GaN buffer layer and the deposited GaN thin film on the sputtered GaN buffer layer were investigated. The high resolution X-ray diffraction result revealed that hexagonal wurtzite structure GaN thin film with (002) preferred orientation and stress value of 0.70 GPa was successfully deposited on sputtered GaN buffer layer. The morphological characterisation revealed that wurtzite GaN thin films deposited on sputtered GaN buffer layer with hexagonal-shaped grains were formed. P -polarised infrared reflectance spectra showed a strong reststrahlen feature of crystalline wurtzite GaN. The transverse and longitudinal phonon modes of wurtzite GaN were clearly identified for the deposited GaN film on sputtered GaN buffer layer. In addition, the E 2 (high) and A 1 (LO) phonon modes were observed at 570.30 and 735.25 cm −1 in Raman spectrum. Highlights: Spin coating growth of GaN thin film on amorphous GaN buffer layer. GaN buffer layer helps to growth crack free and highly c -oriented wurtzite GaN. Smooth grains with hexagonal-shaped was obtained from FESEM image.